Commodification of Women Characters in Indian and Greek Mythology with Special Reference Chitra Banerjee Divakaruni and Amanda Elyot - Bhagyasri, D. Mani; Vijayanand, Dr. A. (The journal of contemporary issues in business and government, 2023)
The papers attempt to explore the feminine themes in Greek and Indian mythological works. This paper looks at how Indian and Greek mythological texts deal with female existence. The authors have compared and contrasted the feminine and masculine gods in Greek and Indian literature. It is clear that female and male gods are deified and treated differently. In Greek literature, the characteristics of each god are shown to be those of destruction and construction. Additionally, the negative characteristics were given to the feminine gods, while the virtues of construction were given to the masculine gods. The paper likewise ponders on the treatment of ladylike and manly divine beings in Indian fanciful texts like the Puranas and the old legends of India like the Ramayana and Mahabharata. The commodification of female existence in Indian folklore is also the subject of this paper, which draws particular attention to the works of Chitra Banerjee Divakaruni and Amanda Elyot.